Occurrence of virulence genes and carbapenemase genes in multidrug resistant clinical isolates of Pseudomonas aeruginosa - Ahsan, Hira; Aslam, Bilal; Nawaz, Zeeshan; Ahmad, Muhammad Zishan; Hussain, Riaz; Naveed, Rasheeha; Baig, Asma; Ataya, Farid Shokry; Fouad, Dalia; Siddique, Abu Baker (The Journal of Infection in Developing Countries, 2026)
Introduction: Multi-drug resistant (MDR) Pseudomonas aeruginosa strains with virulence characteristics have high morbidity and mortality rates. This study aimed to examine the prevalence of antibiotic resistance, virulence factors, and carbapenemase genes in clinical samples. Methodology: 400 clinical samples (200 UTI+200 wound samples) were collected from hospitalized patients, targeting P. aeruginosa. Results: Out of 400 samples, 162 (40%) were found positive for P. aeruginosa, and they revealed significant resistance, with 55% classified as multidrug-resistant. Ceftazidime and Imipenem showed the highest resistance rate. Notably, 90% isolates were resistant to Tobramycin and Amikacin, while only 15-25% of isolates were sensitive to several antibiotics. The samples showed that 101 isolates (62% of the total) had the algD gene. Of these, 78% were found to be resistant to multiple drugs. Carbapenemase gene prevalence varied, with IMP (77.27%) being the most common, followed by TEM (63.63%) and NDM (43.18%). The detected exo enzyme genes in 67.9%-88.88% of isolates, with toxA being the most prevalent at 88.88%. Wound isolates showed higher virulence gene frequencies compared to urine isolates. Conclusions: The misuse/overuse of antibiotics, poor hygiene, and errors of health care personnel were the main factors that significantly increased the prevalence of MDR P. aeruginosa. Hospitals should craft and implement a specific control strategy to reduce the distribution of MDR P. aeruginosa. The MDR isolates expressed exoenzymes-encoding genes as compared to the drug-susceptible isolates. The prevalence of these virulence genes was higher in wound isolates as compared to UTIs. This study indicates that exoenzymes-encoding genes are associated with drug resistance in P. aeruginosa.